Effects of palm olein and palm stearin on cecal and fecal microbiota of C57BL/6J mice under low and high fat intakes. (15th March 2023) - Wan, Liting; Li, Lin; Zhang, Xia; Li, Bing; Harro, Janette M.; Shirtliff, Mark E.
Graphical abstract: Highlights: Increasing dietary PS but not PO intake to a high-fat level favored Firmicutes over Bacteroidetes. Only at high fat intake can PS (vs PO) significantly change the gut microbiota profiles. HFPS intake significantly enriched bacteria that may use bile and fat as metabolic substrates. The significantly reduced impacts of PO (vs PS) on gut microbiota may be due to its high absorption rate in vivo . Abstract: This work aimed to study the effects of dietary lipid composition and content on cecal and fecal microbiota of mice fed the following diets for 8 weeks: palm olein (PO)-based low-fat diet, PO-based high-fat diet, palm stearin (PS)-based low-fat diet, and PS-based high-fat diet. Increasing the dietary PS level favored the growth of Firmicutes over Bacteroidetes in the cecum and feces. In addition, it significantly elevated the total lipid ( p < 0.01) and bile acid content ( p < 0.01) in feces, resulting in the enrichment of fat-degrading and bile-acid tolerant genera within the families Ruminococcaceae and Lachnospiraceae. Although increasing the PO intake also caused obesity in mice, it did not affect the microbial structure. When fat intake is constant, only at a high-fat level can PS (vs PO) induce the above-mentioned microbial shifts. These results highlighted the combined roles of lipid quality and quantity on the gut microbiota.